Cost-free feed-in tariffs for renewable energy deployment in Spain. (September 2015) - Gallego-Castillo, Cristobal; Victoria, Marta
Abstract: Feed-in-tariff (FIT) schemes have been widely employed to promote renewable energy deployment. While FITs may be perceived by consumers as an extra cost, renewable energies cause a noticeable price reduction in wholesale electricity markets. We analyse both effects for the case of the Spanish electricity market during 2010. In particular, we examine the level of FITs that makes savings and extra costs to be similar on an hourly basis. Results are obtained for a wide range of renewable generation scenarios. It is found that FITs with null extra costs for consumers are in the range of 50–80 €/MWh. Some of the side-effects of a high penetration of renewable energy in the market are analysed in detail and discussed. Highlights: An innovative methodology to estimate the merit-order effect is introduced. FITs in the range of 50–80 €/MWh are compensated by savings in the electricity market. Higher renewable energy shares does not involve increasing electricity prices.